Immunobiology : the immune system in health and disease - Janeway, Charles A. (Curent Biology, 1999)
The central thesis of this book is that the immune system exists to protect the host from infection and that its evolutionary history was shaped by this challenge. Other aspects of immunology (eg allergy, graft rejection for example) are variations on the basic protective function. The book summarises the basic immunological concepts and introduces the "main players". It deals with main aspects of adaptive immunity. It integrates the material at the level of the complete organism in both health and disease.